Effect of Preservatives on IgG Aggregation, Complement-activating Effect and Hypotensive Activity of Horse Polyvalent Antivenom Used in Snakebite Envenomation - García González, Mildred (2002)
Intravenous administration of antivenoms is associated with early adverse reactions in a number of cases, but the causes of this phenomenon are still unclear. The effect of preservatives (phenol and thimerosal) on IgG aggregate and dimer formation, in vitro complement-activating effect and hypotensive activity of a whole IgG horse liquid polyvalent antivenom, produced by caprylic acid fractionation, was assessed. These parameters were studied since they have been associated with the development of early adverse reactions to the administration of antivenoms and human immunoglobulins. After a three-year storage period at 4 degrees C, antivenoms with preservatives had an increased content of IgG aggregates and dimers when compared with antivenom devoid of phenol and thimerosal. These observations correlate with a slight increment in the turbidity of preservative-containing antivenoms. The three antivenoms studied (formulation: no preservatives; with phenol and thimerosal; with thimerosal alone) activated human complement in vitro, with only minor quantitative differences among them. When antivenoms were administered as a bolus intravenous injection in rats, a rapid and prominent hypotension of short duration was observed after injection of phenol-containing antivenom, whereas such an effect was absent in antivenom free of preservative and in the one containing only thimerosal. Bolus injection of saline solution with phenol resulted in a similar hypotension, indicating that the effect is due to phenol. However, when phenol-containing antivenom was diluted 1:5 with saline solution before infusion, as occurs in the clinical use of this product, no hypotension was observed. Our results stress the need to evaluate the effects of preservatives on the physicochemical and pharmacological characteristics of antivenoms.